The Effect of Discount Live-Stream and Bundling Product on Impulse Buying Through Positive Emotions - Nur Azizah Maulidia; Nur Afifah; Wenny Pebrianti; Juniwati Juniwati; Heriyadi Heriyadi (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of Discount Live Streaming and Bundling Products on Impulse Buying through Positive Emotion as an intervening variable among TikTok Shop users in Indonesia. Methodology/approach: This was a causal research design. The collected data were analyzed using the SEM-PLS method through the SmartPLS4 application, with a total of 280 respondents. Results: Discount live streaming has a positive and significant effect on positive emotions. Product bundling also has a positive and significant effect on positive emotions. Both discount live streaming and product bundling have a direct effect on impulse buying; however, this effect becomes stronger when mediated by positive emotions. Conclusions: All hypotheses proposed in this study were accepted, indicating that positive emotions play an important role in strengthening the influence of discount live streaming and product bundling on impulse buying. Limitations: This study was limited to respondents aged 17–40 years and predominantly from the Kalimantan region. It did not consider other variables, such as urgency perception, social proof, or trust. Contributions: This study develops and tests a conceptual model that integrates digital sales promotion factors (discounts and bundling) with psychological aspects (positive emotions) to explain impulsive buying behavior.